2021
DOI: 10.1002/anie.202100054
|View full text |Cite
|
Sign up to set email alerts
|

An Endoplasmic Reticulum Specific Pro‐amplifier of Reactive Oxygen Species in Cancer Cells

Abstract: The folding and export of proteins and hydrolysis of unfolded proteins are disbalanced in the endoplasmic reticulum (ER) of cancer cells, leading to so-called ER stress. Agents further augmenting this effect are used as anticancer drugs including clinically approved proteasome inhibitors bortezomib and carfilzomib. However, these drugs can affect normal cells, which also rely strongly on ER functions, leading, for example, to accumulation of reactive oxygen species (ROS). To address this problem, we have devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…We confirmed that all these cells contain the high level of ROS. Therefore, they were expected to be sensitive to ROS amplifying drugs [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Due to the slow kinetics of action of 2c observed in A2780 cells ( Table S2, SI ), incubation times of 48–96 h were selected.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We confirmed that all these cells contain the high level of ROS. Therefore, they were expected to be sensitive to ROS amplifying drugs [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Due to the slow kinetics of action of 2c observed in A2780 cells ( Table S2, SI ), incubation times of 48–96 h were selected.…”
Section: Resultsmentioning
confidence: 99%
“…These data thus confirm the high mitochondria-specificity of 2c. Since 2c is an NAAF prodrug, another expected effect would be the amplification of ROS in cells [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. To evaluate whether this is the case, we used three different probes: the nonspecific probe 5-(6-)chloromethyl-2′,7′-dichlorodihydrofluorescein diacetate (CM-DCFH-DA) for the measurement of total ROS (tROS), the mitochondria-specific probe Red Mitochondrial Superoxide Indicator (MitoSOX) for the measurement of mitochondrial ROS (mROS) and 7-(diethylamino)coumarin-3-cerbohydrazide (DCCH) for monitoring ROS-induced formation of intracellular carbonyl-derivatives ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations